A low-cost uncooled infrared microbolometer detector in standard CMOS technology. - Tezcan, D.S (IEEE Transactions on electron devices)
This paper reports the development of a low-cost uncooled infrared microbolometer detector using a commercial 0.8 μm CMOS process, where the CMOS n-well layer is used as the infrared sensitive material. The n-well is suspended by front-end bulk-micromachining of the fabricated CMOS dies using electrochemical etch-stop technique in TMAH. Since this approach does not require any lithography or infrared sensitive material deposition after CMOS fabrication, the detector cost is almost equal to the CMOS chip cost. The n-well has a TCR of 0.5-0.7%/K, relatively low compared to state-of-the-art microbolometer materials; however, it has negligible 1/f noise due to its single crystal structure. The use of polysilicon interconnects on the support arms instead of metal reduces the overall pixel TCR to 0.34%/K, but provides a better performance due to improved thermal isolation. Based on this pixel, a 16 × 16 prototype focal plane array (FPA) with 80 μm × 80 μm pixel size and 13% fill factor has been implemented, where built-in diodes are used to simplify array scanning, at the expense of reduced overall pixel TCR of 0.24%/K. The n-well microbolometer array with a simple readout scheme provides a responsivity of 2000 V/W, a detectivity of 2.6 × 108 cmHz12//W, and an estimated NETD of 200 mK at 0.5 Hz frame rate. Considering that this performance can be further improved with low noise readout circuits, the CMOS n-well microbolometer is a cost-effective approach to implement very low-cost uncooled infrared detector arrays with reasonable performance.